2013
DOI: 10.5863/1551-6776-18.3.220
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Pediatric Antibiotic Standard Dosing Table on Dosing Errors

Abstract: OBJECTIVES The goal of this study was to compare the rate of dosing errors for antibiotic orders in pediatric patients before and after the implementation of an antibiotic standard dosing table with precalculated dosage for different weight ranges at a tertiary care hospital. METHODS A retrospective study of 300 antibiotic prescriptions for pediatric patients in three different settings (ambulatory care, inpatient, and emergency department) at a tertiary care hospital assessed the appropriateness of antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Inability to recycle has been found to be the result of two major factors namely, short stability of IV preparations and using unstandardized doses. Implementing dosing standardization and polices that guide the medication use process in the hospital setting have also been found to be important in minimizing medication errors and promoting medication safety and control [18].…”
Section: Discussionmentioning
confidence: 99%
“…Inability to recycle has been found to be the result of two major factors namely, short stability of IV preparations and using unstandardized doses. Implementing dosing standardization and polices that guide the medication use process in the hospital setting have also been found to be important in minimizing medication errors and promoting medication safety and control [18].…”
Section: Discussionmentioning
confidence: 99%
“…In adult patients, drug doses are standardized. However, in children, drugs are prescribed based on the patient's age, weight, body surface area, and/or clinical condition (21). For pediatric antibiotic regimens, doses are usually weight-based, and therefore careful calculation is required to ensure correct dosage.…”
Section: General Pediatric Antibiotic Dosingmentioning
confidence: 99%
“…Pediatric patients therefore are at a higher risk than adults for experiencing the effects of dosing errors; this may result in subtherapeutic antibiotic dosing causing treatment failure and the emergence of resistant organisms (22) or supratherapeutic dosing and toxicity. Many institutions performing pediatric interventional procedures have an antibiotic dosing standardization that minimizes the risk of calculation errors and reduces the time required for dose calculation by the prescriber (21). Appendix C (available online on the article's Supplemental Material page at www.jvir.…”
Section: General Pediatric Antibiotic Dosingmentioning
confidence: 99%
“…Many studies to reduce PEs and AEs in hospitalized children have investigated the impact of a single intervention such as education or training . The results of those studies showed that none of the interventions were superior in terms of error reduction.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Many studies to reduce PEs and AEs in hospitalized children have investigated the impact of a single intervention such as education or training. [18][19][20][21][22][23][24][25][26][27][28][29][30] The results of those studies showed that none of the interventions were superior in terms of error reduction. The processes of prescribing and administration are complex because the causes of errors are multifactorial 8 and different conditions for behaviours are involved.…”
Section: What Is Known and Objectivementioning
confidence: 99%